Real Oil Prices, Real Economic Activity, Real Interest Rates, and the US Dollar: A Cointegration Analysis with Structural Breaks - Tamakoshi, Go; Hamori, Shigeyuki (Journal of Reviews on Global Economics, 2012)
Abstract: In this paper, we examine the relationship among real oil prices, global economic activity, real value of the US dollar, and real interest rates during the period 1988:1 to 2011:12. We employ the Gregory and Hansen (1996) cointegration test with structural breaks to investigate the long-run equilibrium and analyze the short-term Granger causality as well. Our findings indicate that real oil prices are cointegrated with the three factors mentioned above and are affected positively by real economic activity and negatively by real interest rates and the real value of the US dollar. We also find significant short-run causality from real economic activity to real oil prices, but no significant causality from real interest rate and real value of US dollar to real oil price is detected. These findings are relevant for both policymakers and investors who wish to conduct forecasts for future oil prices on the basis of a solid understanding of its key drivers.